A Escola Militar do Realengo e a formação do oficial do Exército Brasileiro (1904 1929) - Marcusso, Marcus Fernandes (Universidade Federal de São Carlos, 2012)
This dissertation is inserted in the area of foundations of Education of the Program of Post-Graduation in Education of the Federal University of São Carlos. The objective of this dissertation is to analyze the Military Academy of Realengo in the period 1913 to 1929, and teaching it in order to characterize the type of officer who sought to form this teaching. Other objectives are to analyze the teaching of Military Academy of Praia Vermelha, the predecessor of EMR in the training of officers, and the study of the conditions of the army and military education in the period before the founding of the EMR between 1905 and 1913. We assume that, between 1913 and 1929, EMR has served as a laboratory of the Army for the experiments about which education /instruction would be ideal for building the Army frame. The primary sources occupy a privileged place in this dissertation, with emphasis on primary sources handwritten, printed, oral and virtual. Source official personnel file, memorialistic reports, interviews and memoirs. The studies allowed the identification of three periods of "educational experiments" in the EMR. The first period, from 1913 to 1918, was essentially marked by the scarcity of resources of all kinds: human, material and disciplinary. The second period from 1918 to 1922, was marked by a wave of modernization that aimed to train an officer with technical knowledge and more advanced practitioners, with a strict discipline and preparation to perform the duties of commanding troops. The third and last period begins in 1922 with the penetration of French officers in the EMR with the drafting of a new regulation for the military school which proposed the formation of an officer who kept their technical and professional knowledge, strict discipline, and readiness for perform the function of commanding troops, but he saw as a prerequisite for the incorporation of these skills a cultural scientific broader than was being offered.
Keywords: Educação militar; Brasil - História - Primeira República; Brasil - educação castrense; Formação do Oficial do Exército; Escola Militar do Realengo; First Republic; Official army training; Military Academy of Realengo; CIENCIAS HUMANAS::EDUCACAO